Measuring Distraction at the Levels of Tactical and Strategic Control: The Limits of Capacity-Based Measures for Revealing Unsafe Visual Sampling Models - Tuomo Kujala; Pertti Saariluoma (Advances in Human-Computer Interaction)
The control theory of driving suggests that driver distraction can be analyzed as a breakdown of control at three levels. Common approach for analyzing distraction experimentally is to utilize capacity-based measures to assess distraction at the level of operational control. Three driving simulation experiments with 61 participants were organized to evaluate which kind of measures could be used to analyze drivers' tactical visual sampling models and the related effects of distraction while searching textual information on in-car display. The effects of two different text types were evaluated. The utilized capacity-based measures seemed to be insufficient for revealing participants' tactical behaviors or effects of text type. The measures of workload or performance did not indicate reliably the differences found between participants' visual sampling strategies or which text type is better for enabling safer task timing behaviors. Visual sampling measures did indicate effects of text type on participants' tactical abilities. Differences in participants' visual sampling strategies leading to different levels of systematicity in visual behaviors can explain the variances in visual sampling efficiency. Displays encouraging unsystematic glance allocation behaviors were found potentially the most distracting in relation to safe visual sampling of in-vehicle displays.